2018
DOI: 10.1038/s41378-018-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Capillary pumping independent of the liquid surface energy and viscosity

Abstract: Capillary pumping is an attractive means of liquid actuation because it is a passive mechanism, i.e., it does not rely on an external energy supply during operation. The capillary flow rate generally depends on the liquid sample viscosity and surface energy. This poses a problem for capillary-driven systems that rely on a predictable flow rate and for which the sample viscosity or surface energy are not precisely known. Here, we introduce the capillary pumping of sample liquids with a flow rate that is constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
(22 reference statements)
0
20
0
1
Order By: Relevance
“…When the pumping liquid is drawn by capillary forces in the absorbent pad, it creates a pressure drop in the sample channel, thereby drawing the sample fluid from the reservoir into the sample channel. They further demonstrated that this micropump can pump fluid of varying viscosity and density with a constant speed ( Figure 5 (d)) [103,104]. In an another study, researchers have suggested the use of a converging tube to increase the capillary flow velocity [105].…”
Section: Design Modification To Facilitate Capillary Pumping Of High mentioning
confidence: 99%
“…When the pumping liquid is drawn by capillary forces in the absorbent pad, it creates a pressure drop in the sample channel, thereby drawing the sample fluid from the reservoir into the sample channel. They further demonstrated that this micropump can pump fluid of varying viscosity and density with a constant speed ( Figure 5 (d)) [103,104]. In an another study, researchers have suggested the use of a converging tube to increase the capillary flow velocity [105].…”
Section: Design Modification To Facilitate Capillary Pumping Of High mentioning
confidence: 99%
“…The different methods adopted in every passively driven type of microuidics are briey covered, so that one can obtain a better and clearer knowledge of previous techniques. [84][85][86] This also throws light on the advantages, ow rates and applications of all the techniques. The limitations of each method are also explained.…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…Surface tension has been explored in various capillary-based microfluidic pumping devices to drive fluid flow in a passive manner (Zimmermann et al 2007 ; Chao and Meldrum 2009 ). A recently presented microfluidic device architecture has been shown to perform capillary-based pumping independent of the surface energy and viscosity of the sample liquid (Guo et al 2018 ). They achieved this using the capillary movement of a known working liquid located downstream of the microfluidic channel pulling the unknown sample liquid.…”
Section: Introductionmentioning
confidence: 99%